The Effectiveness of a Training Program For Parents on Awareness of Alternative Treatments For Attention Deficit Hyperactivity Disorder - Bahkali, Samirah Abdu Ahmed (Dirasat: Educational Sciences, 2025)
Objectives: This study aimed to design a training program to enhance parents' awareness of alternative treatments for attention deficit hyperactivity disorder (ADHD) and to verify its effectiveness. Methods: A quasi-experimental approach was applied to a sample of 30 parents of children with ADHD. The study utilized two main tools: a scale measuring parents’ awareness of ADHD treatment methods and a training program designed to increase awareness of alternative treatments for ADHD. Results: The findings indicated statistically significant differences between pre- and post-measurements of parents’ awareness levels. The training program effectively improved understanding of various ADHD-related interventions, including nutrition and herbal approaches, physical activities and fine arts, as well as behavioral and occupational therapies. Conclusions: The study highlighted the importance of educational programs in increasing parental awareness of ADHD treatment alternatives, particularly given the growing interest in non-pharmacological interventions for children with ADHD.